Moment analysis of metabolic heterogeneity: conjugation of benzoate with glycine in rat liver studied by multiple indicator dilution technique - Schwab, Andreas J; Tao, Lei; Kang, Manjinder; Meng, Lingjie; Pang, K Sandy (The Journal of pharmacology and experimental therapeutics, 2003)
Metabolic zonation was assessed with the multiple indicator dilution (MID) technique in the single-pass perfused rat liver with use of moment analysis of the formed metabolite (M) data. During single-pass, retrograde rat liver perfusion with 17 Awake M benzoate, a bolus containing tracer preformed metabolite (PM) [(3)H]hippurate was injected rapidly into the hepatic vein at 20 min postperfusion, followed by injection of a second bolus containing [(14)C]benzoate at 30 min. Both doses also contained noneliminated reference indicators ((51)Cr-labeled RBCs, (125)I-labeled albumin, [(14)C]- or [(3)H]sucrose, and (2)H(2)O). The steady-state extraction ratio of benzoate, the area under the curve (AUC) and its mean transit time (MTT) during retrograde flow were identical to those previously observed for prograde flow. Values of AUC(PM) and MTT(PM) and AUC(M) were also similar to previously published prograde data, but the MTT(M) with retrograde perfusion was smaller than that for prograde perfusion. This, according to theory based on the tubes-in-series model, was consistent with perivenous enrichment of glycination activity when transport of drug was even and when the ratio of drug influx/efflux coefficient exceeded that for metabolite. Similar benzoate transport in periportal, homogeneous and perivenous isolated rat hepatocytes existed, and the influx/efflux coefficients (partition ratio) of benzoate from MID indeed exceeded that of hippurate. However, metabolism by zonal hepatocytes failed to reveal the anticipated metabolic zonation, and this is likely due to the shallow gradient of metabolic activity. The study demonstrates that moment theory is useful in delineating the perivenous enrichment of glycine conjugation activity.